RabGAP1L modulates Rab7A and Rab10 to orchestrate cell-autonomous immunity - Atsuko Minowa-Nozawa; Takashi Nozawa; Kazunori Murase; Ichiro Nakagawa (Cell Reports)
Summary: Cell-autonomous immunity protects cells by utilizing membrane trafficking to detect and counteract diverse microbial pathogens, including selective autophagy and extracellular expulsion. However, the mechanisms underlying the mutual regulation among these systems has remained unknown. Here, we demonstrate that Rab GTPase-activating protein 1-like (RabGAP1L) modulates cell-autonomous immune responses via inactivation of two distinct Rab GTPases during group A Streptococcus (GAS) infection. Confocal microscopy analyses revealed that Rab7A positively regulates selective autophagy induction against GAS by facilitating endolysosomal trafficking and that Rab7A and Rab10 negatively regulate GAS expulsion from infected cells by inhibiting Rab11A-positive recycling endosome formation. RabGAP1L suppressed these pathways via inactivation of Rab7A and Rab10. By contrast, ATG7 and ATG5 knockout, resulting in autophagy deficiency, increased RabGAP1L-dependent bacterial expulsion from infected cells via the endocytic recycling pathway. Our findings suggest a regulatory mechanism of cell-autonomous immunity mediated by RabGAP1L, which contributes to the efficient elimination of intracellular pathogens.